Characterization of a single 90-degrees 'UREAD' energy channel - LUPOI, ROCCO (My University, 2006)
Most engineering products are designed to either deliver or withstand a specific maximum force or level of energy. It is important however that the design of a struct ure or a machine incorporates an external or internal mechanism to overcome excessive loading, so as to reduce human discomfort and unsafe operations. Most high-energy absorption devices are not re-usable and have rebound forces comparable to those that being absorbed. This paper examines the validity of a new concept which has been implemented into a Universal Re-usable Energy Absorption Device – ‘UREAD’. The process uses a passageway of a constant cross sec tion. Experiment s were applied to devices of a single 90-degrees passageway that is constructed from intersecting cha nnels. The experiments were carried out using different materials and di fferent channel dimensions. Th e results showed a typical patt ern of deformation that is associated with a continuous in tense shearing with a regular force displacement diagram. Patterns of deformation zones were investigated by the Finite Element Analysis(FEA), and th e predictions showed a yielding process that is dominated by shearing zones.
ICRASH 2006
Keywords: Excesssive loading